Factors Affecting Mathematics Problem Solving Ability in Online Learning - Azhar Majid Hidayat; Al Jupri; Dadang Juandi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2021)
At the beginning of 2020, a pandemic occurred in all countries, one of which was Indonesia and it had an impact on the learning carried out in Indonesia. Learning that is usually done face-to-face has turned into online learning. This study aims to determine the factors that affect online learning of class XI students on their mathematical problem-solving abilities. This research uses descriptive qualitative research methods. The population in the study was simultaneously used as a sampling (Total Sampling) with a total of 52 students. Data were collected through tests and questionnaires. Based on the results of research on the mathematical problem solving ability of students at one of the senior high schools (SMA) in the city of Bandung in online learning 50% has a medium category, so that online learning is going well, the problem only occurs in indicators checking and testing calculations or solutions. Internal factors and external factors have a strong influence during online learning.